Clinical and dermoscopic clues to differentiate pigmented nail bands: an International Dermoscopy Society study. (15th November 2016) - Benati, E.; Ribero, S.; Longo, C.; Piana, S.; Puig, S.; Carrera, C.; Cicero, F.; Kittler, H.; Deinlein, T.; Zalaudek, I.; Stolz, W.; Scope, A.; et al.
Abstract: Background: Longitudinal melanonychia might be difficult to differentiate and the use of dermoscopy can be useful for the preoperative evaluation and management decision. Objectives: The aim of our study was to investigate clinical and dermoscopic criteria of acquired longitudinal melanonychia in adults to identify the best predictors of melanoma using a multivariate analysis and to explore eventual new dermoscopic criteria for nail melanoma diagnosis. Methods: In this retrospective observational study, 82 histopathologically diagnosed, acquired nail pigmented bands were collected and examined. All variables were included in the analysis and examined as possible predictors of nail melanoma. Both univariate and multivariable analyses have been performed. Results: Among 82 cases, 25 were diagnosed as nail melanoma and 57 as benign lesions (including 32 melanocytic nevi and 25 benign melanocytic hyperplasia). Melanoma cases were significantly associated with a width of the pigmented band higher than 2/3 of the nail plate, grey and black colours, irregularly pigmented lines, Hutchinson and micro‐Hutchinson signs, and nail dystrophy. Granular pigmentation, a newly defined dermoscopic criterion, was found in 40% of melanomas and only in 3.51% of benign lesions. Conclusions: Dermoscopic examination of longitudinal melanonychia provides useful information that could help clinicians to improve melanoma recognition.